Avaliação da frequência fundamental de vibração de lajes alveolares - Martins, Daniele dos Santos (2023)
Prestressed hollow core slabs are an important alternative for flooring in prefabricated build-ings, as they overcoming large spans, have low weight and are easily assembled. However, these same advantages can result in flexible floors, subject to excessive vibrations, causing dis-comfort to the building users and, in extreme cases, may result in the collapse of the structure. In this sense, it appears that there are few studies in the academic environment that deal with the analysis of vibrations in floors with unidirectional prestressed hollow core slabs. In the existing literature, there is no analytical formulation or analysis parameter for unidirectional hollow core slabs. The natural frequencies of vibration can be obtained experimentally, with the excitation of the structure through impact and the use of accelerometers to record the data. However, measurements on site are often difficult and costly. One way to predict the vibration frequencies of a structure is through numerical modeling with the aid of the finite element method (FEM). The objective of this work was to carry out the experimental measurement of the fundamental frequency of vibration of three unidirectional prestressed honeycomb panels with three different panel configurations, spans, prestressing, alveoli arrangement, boundary conditions with thicknesses of 15 cm and 20 cm. For the characterization of the concrete, spec-imens were molded to measure the compressive strength and static modulus of elasticity. The experimental data were used to calibrate the numerical models performed via FEM with the aid of the ABAQUS software. With the models calibrated, numerical simulation was carried out for different spans in each geometry, maintaining the properties of the panels that were experi-mentally tested. From the results obtained, an equation was proposed that allows estimating the natural frequency of the first mode of flexural vibration considering span, modulus of elasticity and thickness of prestressed hollow core slab panels for the geometries studied. With the results of the frequencies obtained experimentally and numerically, it was observed that the frequency decreases with the increase of the span. The panels under study presented values close to ex-perimental and numerical frequency, with emphasis on the 20 cm thick panel. The equations proposed to obtain the fundamental frequency for panels of 15 cm and 20 cm in isolation and the panel of 15 cm in solidarity presented R² very close to 1, guaranteeing reliability in the results